DECISION-MAKING ALGORITHMS BASED ON DETERMINING THE LEVEL OF STUDENT KNOWLEDGE - Navruza Irmukhamedova (Web of Journals Publishing, 2025)
In this article, we create decision-making algorithms based on determining the level of student knowledge. The developed system is implemented by means of a non-deterministic logic apparatus in the process of summarizing solutions for evaluating the effectiveness of quality control of students' knowledge. We can express it through practical experiences in creating an expert system that makes firm conclusions based on established criteria for evaluating the effectiveness of education. We will consider the issue of using expert systems in the educational process. The widespread use of Internet technologies ensures the development of new forms of education along with new forms of education, including distance systems or “e-learning systems”, In this case, the assessment of the effectiveness of education and the control of the quality of the knowledge received by students has become a rather complex multi-criteria issue. It is required to solve it in modern ways. One of these approaches is the application to the training process of an expert system using a non-deterministic logic device.